The Effects of the Reverse Current Caused by the Series Compensation on the Current Differential Protection - Cui Tang; Xianggen Yin; Xuanwei Qi; Zhe Zhang; Minghao Wen (The Scientific World Journal)
The series capacitor compensation is one of the key technologies in the EHV and UHV long distance power transmission lines. This paper analyzes the operation characteristics of the main protection combined with the engineering practice when the transmission line overcompensation due to the series compensation system is modified and analyzes the influence of the transition resistance and the system operation mode on the current differential protection. According to the simulation results, it presents countermeasure on improving the sensitivity of differential current protection.